2020
DOI: 10.1186/s13002-020-00389-x
|View full text |Cite
|
Sign up to set email alerts
|

The governance of traditional medicine and herbal remedies in the selected local markets of Western Kenya

Abstract: Background: A lot of emphasis is often placed on modern governance systems and little or no attention is given to traditional governance practices which remain largely undocumented. The study aimed at finding out important traditional and modern governance practices that regulate traditional medicine sector in Western Kenya. Materials and methods: The study was carried out in selected market centres of Western Kenya where the identified traditional medicine practitioners (TMPs) sell their traditional medicine.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 64 publications
7
33
1
1
Order By: Relevance
“…To monitor the practice of traditional medicine needs the legalized system, special spaces, and procedures. This study is different from the report for western Kenya [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…To monitor the practice of traditional medicine needs the legalized system, special spaces, and procedures. This study is different from the report for western Kenya [ 21 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This enforces the knowledgeable persons to go away from traditional healthcare systems or distant places where not frequently contact with, consequently, to the loss of healing knowledge. This study result agrees with the report elsewhere in Ethiopia [ 10 ], reported to Jigjiga of eastern Ethiopia [ 45 ], for western Kenya [ 21 ], and elsewhere [ 71 , 72 ]. The traditional medicine practice has to get formal and legal ground as well as integrate with the modern system to serve the community.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…En la presente investigación el conocimiento tradicional de las plantas no varía significativamente respecto a la etnia y el género, y lo inverso ocurre en los rangos de edad. Chebii et al (2020) demuestra que las abuelas son las encargadas de enseñar las prácticas de la medicina tradicional a las nuevas generaciones en Kenia; en el estudio efectuado en Ecuador, son los padres, en particular las madres, los que desempeñan una función rectora en la transmisión generacional del saber etnobotánico. La literatura ratifica que en este sector imperan las mujeres en relación a los hombres (Lulekal et al, 2013;Ríos et al, 2017;Campos-Saldaña et al, 2018;Duque et al, 2018;Lara et al, 2019;Vinagre et al, 2019;Rosero-Gómez et al, 2020;Ribeiro Magno-Silva et al, 2020), y dentro del sector femenino la distribución del conocimiento y el aprendizaje etnobiológico no es homogénea; su cúmulo se incrementa con la edad (Rosero-Gómez et al, 2020), y está influenciada por el nivel educacional y posición social del individuo (Campos-Saldaña et al, 2018).…”
Section: Discussionunclassified